Chiral phosphorothioate analogues of B-DNA. The crystal structure of Rp-d[Gp(S)CpGp(S)CpGp(S)C]. - Cruse, W; Salisbury, SA; Brown, T; Cosstick, R; Eckstein, F; Kennard, O (1986)
The compound Rp-d[Gp(S)CpGp(S)CpGp(S)C], an analogue of the deoxyoligomer d(G-C)3, crystallizes in space group P2(1)2(1)2(1) with a = 34.90 A, b = 39.15 A and c = 20.64 A. The structure, which is not isomorphous with any previously determined deoxyoligonucleotide, was refined to an R factor of 14.5% at a resolution of 2.17 A, with 72 solvent molecules located. The two strands of the asymmetric unit form a right-handed double helix, which is a new example of a B-DNA conformation and brings to light an important and overlooked component of flexibility of the double helix. This flexibility is manifest in the alternation of the backbone conformation between two states, defined by the adjacent torsion angles epsilon and zeta, trans . gauche-(BI) and gauche-. trans (BII). BI is characteristic of classical of B-DNA and has an average C(1') to C(1') separation of 4.5 A. The corresponding separation for BII is 5.3 A. Each state is associated with a distinct phosphate orientation where the plane of the PO2 (or POS) group is alternately near horizontal or vertical with respect to the helix axis. The BI and BII conformations are out of phase on the two strands. As a consequence, on one strand purine-pyrimidine stacking is better than pyrimidine-purine, while the converse holds for the other strand. At each base-pair step, good and bad stacking alternate across the helix axis. The pattern of alternation is regular in the context of a fundamental dinucleotide repeat. Re-examination of the B-DNA dodecamer d(C-G-C-G-A-A-T-T-C-G-C-G) shows that the C-G-C-G regions contain the BI and BII conformations, and the associated dual phosphate orientation and asymmetric base stacking. Different mechanisms are used in the two structures to avoid clashes between guanine residues on opposite strands, a combination of lateral slide, tilt and helical twist in the present structure, and base roll, tilt and longitudinal slide (Calladine rules) in the dodecamer. The flexibility of the phosphate orientations demonstrated in this structure is important, since it offers a structural basis for protein-nucleic acid recognition.